Workplace technology adoption and organizational change in Nigerian customs service - Obadiah, Kurutst Rika; Ugwu, Kelechi Enyinna; Asiabaka, Pauline Ihuoma; Njoku , Odinakachi Charles; Onyechere, Patricia Onyinyechi (Journal of Commerce, Management, and Tourism Studies, 2025)
The general objective of this research delves into workplace technology adoption and organizational change in the selected Nigerian Customs Service, South-South Zone. The specific objective is to assess the level of the relationship between digital literacy and employee engagement. The study used a correlational survey design and questionnaire to collect data. The total population of the study comprised 565 employees. The sample size was determined statistically using the Taro Yamane formula and calculated as 234. A proportional allocation formula determines the number of surveys for each stratum- River, Bayelsa, Edo, Akwa Ibom, and Delta State, Nigeria.  Out of 234 copies of a questionnaire sent to the participants, only 205 were returned and utilized for the study while the remaining 29 copies were not used. The hypotheses were statistically tested and analyzed using Pearson correlation methods at a 5% significance level. The findings of the research hypothesis revealed that digital literacy level (skills) positively correlates with employee engagement. This result confirms a positive result with the value of (p= .000, r = .991, N = 205).  The researcher recommends that organizations should increase investment in continuous technological upgrades. The Nigerian Customs Services should prioritize continuous investment in modern technologies that align with global best practices. These include blockchain for trade transparency, AI-powered analytics, and IoT for real-time tracking of goods. Regular training programs should be implemented to enhance staff digital literacy and ensure the smooth adoption of new technologies. Training should focus not only on technical skills but also on change management to overcome resistance.